Efektifitas Sidang Keliling dalam Meningkatkan Kesadaran Hukum Masyarakat; Studi Kasus Sidang Keliling Pengadilan Agama Muara Labuh dalam Penyelesaian Perkara Perceraian - Noferi, Hendri (Jurnal AL-AHKAM, 2019)
Sidang keliling was conducted outside the courthouse, in a location far from the Religious Courts. The role of sidang keliling in increasing community le- gal awareness can be seen from the number of cases before and after. The sidang keliling facilitates, eases costs, and is efficient during the trial process. Hence, sidang keliling received a positive response which was shown by the large public interest in divorce cases. The roundtable session of the Muara Labuh Religious Court for Sangir Subdistrict, Sangir Jujuan, Sangir Batang Hari, Sangir Balai Janggo, Koto Parik Gadang Diateh District (KPGD) and Pantai Cermin Subdistrict are far from Muara Labuh Religious Courts and are at risk of accidents. Sidang keliling is arranged in the Supreme Court Letter of Excerpt (SEMA) No. 10 of 2010 concerning guidelines for legal aid provid- ers in appendix B for the Religious Courts environment, as well as Supreme Court Regulation No. 1 of 2014 concerning guidelines for the provision of le- gal assistance to disadvantaged communities in the courts. Legal socialization from the judges of the Muara Labuh Religious Court in the mobile court that can foster public legal awareness of the importance of legal divorce. Divorced couples officially remarry according to the rules of marriage in the Republic of Indonesia.